Polymer nanotube nanocomposites : synthesis, properties, and applications - Mittal, Vikas (Hoboken, N.J. : Wiley, 2010)
'The purpose of this edited book is to assimilate contributions from a variety of senior scientists in the field of polymer nanotube composites technology to shed light on the recent advances in these commercially important areas of polymer technology. It sums up recent advances in nanotube composite synthesis technology, provides basic introduction to polymer nanotubes nanocomposite technology for the readers new to this field, provides valuable insights for the use of technologies for polymer nanocomposites for commercial application, and features chapters from the most experienced researches in the field'--
'The purpose of this edited book is to assimilate contributions from a variety of senior scientists in the field of polymer nanotube composites technology to shed light on the recent advances in these commercially important areas of polymer technology. It sums up recent advances in nanotube composite synthesis technology, provides basic introduction to polymer nanotubes nanocomposite technology for the readers new to this field, provides valuable insights for the use of technologies for polymer nanocomposites for commercial application, has chapters targeted from the most experienced researches in the field and aims to bridge the deficiency of a meaningful text on the matter'--
Includes bibliographical references and index.
Keywords: Nanotubes; Nanocomposites (Materials); Polymers